Identifying Eligibility for Specialist Intervention in COPD from UK Primary Care Data: A “Treatable Traits” Approach - Ward TJ; John C; Williams AT; Batini C; Greening NJ; Tobin MD; Steiner MC (International Journal of COPD)
Thomas JC Ward,1– 3 Catherine John,2,4 Alexander T Williams,4 Chiara Batini,2,4 Neil J Greening,1– 3 Martin D Tobin,2,4 Michael C Steiner1– 3 1Department of Respiratory Sciences, University of Leicester, Leicester, UK; 2University Hospitals of Leicester, Leicester, UK; 3Institute for Lung Health, National Institute for Health Research Leicester Biomedical Research Centre – Respiratory Glenfield Hospital, Leicester, UK; 4Department of Population Health Sciences, University of Leicester, Leicester, UKCorrespondence: Thomas JC Ward, Institute for Lung Health, NIHR Respiratory Biomedical Research Centre Glenfield Hospital, Groby Road, Leicester, LE3 9QP, UK, Email tom.ward@leicester.ac.ukBackground: Specialist intervention in COPD is often reactive, resulting in inequalities in the provision of care. A proactive approach, in which individuals with modifiable disease are identified from primary care records, may help to tackle this inequality in access.Aim: To estimate the prevalence of “treatable traits” in COPD in a primary care research database and to assess health service usage.Methods: We performed a secondary analysis of individuals with either 1) a primary care diagnosis of COPD or 2) obstructive spirometry and history of ever smoking in a large observational study recruiting individuals aged 40– 69 years old in Leicestershire, UK. Spirometry, height, weight and smoking history were collected prospectively and linked to individuals’ primary care records. “Treatable traits” were identified from primary care records (frequent exacerbations, current smoking, low body mass index, respiratory failure, severe breathlessness, potential suitability for lung volume reduction or psychological comorbidity). Differences in demographics and health usage between those with and without “treatable traits” were assessed.Results: In total, of the 347 individuals with COPD, 186 had at least one “treatable trait”. Compared to those without treatable traits, individuals with treatable traits were younger (61 vs 64 years, p< 0.001), had more severe airflow obstruction (FEV1 86% vs 94% predicted, p=0.002), higher eosinophil count (0.32 vs 0.27 cells/μL, p=0.04) and were more socioeconomically deprived (UK Indices of Multiple Deprivation decile 4.3 vs 5.8, p< 0.001). Individuals with treatable traits had a higher annual primary care health usage (47 vs 30 visits per year, p=0.001). Referrals rates to specialist respiratory services were low in both groups.Conclusion: Treatable traits are common in COPD and can be identified from routinely collected primary care data. Treatable traits are associated with younger age and greater deprivation. These individuals pose a significant burden to primary care yet are rarely referred to specialist respiratory services.Keywords: integrated care, chronic respiratory disease, treatable traits